Monitoring Hama Kumbang Tanduk (Oryctes rhinoceros) Pada Tanaman Aren Di Padukuhan Gondang, Wukirsari, Cangkringan, Sleman - Achmad Himawan; Ismiasih; Resna Trimerani; Fadly Alamsyah; Fadilatun Nisa (Politeknik Piksi Ganesha Indonesia, 2026)
The sugar palm is a commodity of high economic value and plays an important role in farmers’ income as well as land conservation. One of the main threats in sugar palm cultivation is the attack of horned beetle pests, which can damage meristem tissue and cause plant death. A community service activity carried out by the PKM Team from Instiper Yogyakarta in Gondang, Sleman, Yogyakarta, aimed to provide counseling and training on horned beetle population monitoring to members of the Ngudi Lestari Farmers Group. Monitoring was performed using Ferotrap pheromone traps. After ten rounds of monitoring, no horned beetles were found in the cultivation area. These results indicate that the horned beetle population in the area remains safe. The Ferotrap counseling and training effectively enhanced the farmers' knowledge and skills in pest management for sugar palm plants.